Stages of economic development and industrial relations patterns the ASEAN case - Sharma, Basu.; International Relations Association. World congress. (7th : 1986 : Germany). (1986)
This study has detected three different patterns of industrial relations evolving in the ASEAN countries. Indonedia largely represent a political pattern, Singapore an accomodative (co-optation being a variation of this) one, and Thailand, Philippines and Malaysia a conflictual one and it has been shown that these patterns correspond closely to different stages of industrialization, thus giving empirical support to the hypothesis developed in the theoretical section of the paper. thus the theoretical arguments developed and the ASEAN evidence presented in this paper clearly indicate that industrial relations patterns will evolve in new industrializing countries may be different from the ones predicted by proponents of labour markets hypothesis as well as the convergence hypothesis.
Introduction -- A theoretical framework -- Industrialization of the ASEAN -- The ASEAN economies -- The labour markets -- New developments in industrial relations in ASEAN: Indonesia, Malaysia, Philippines, Singapore, Thailand -- Variations in patterns -- Concluding remarks.
Photocopy.
International Relations Association. 7th World congress. Hamburg, Federal Republic of Germany, 1-4 Septmeber 1986. (7th : 1986 : Germany)
Includes bibliographical references (leaves 9-10)
Keywords: Industrial relations -- Southeast Asia; Industrial relations -- Indonesia; Industrial relations -- Malaysia; Industrial relations -- Philippines; Industrial relations -- Singapore; Industrial relations -- Thailand